Development Innovative Work Behavior for Companies? Analysis of Self-Efficacy, Organizational Justice, and Psychological Empowerment as Predictors - Kaharuddin, Kaharuddin; Sofiyan, Sofiyan; Sudirman, Acai (Universitas Pendidikan Ganesha, 2024)
This study aims to analyze the effect of self-efficacy, organizational fairness, and psychological empowerment on innovative work behavior of employees at state banks. This study uses a quantitative approach with research instruments and quantitative data analysis to test predetermined hypotheses. The research data were obtained through documentation instruments and distribution of online questionnaires to 150 employees of state-run banks, selected using purposive sampling methods. The results showed that self-efficacy and psychological empowerment had a positive and significant influence on employees' innovative work behavior. However, organizational fairness does not significantly affect innovative work behavior. The implication of this finding is the importance of companies, especially bank managers, to pay attention to the fair and transparent application of organizational justice in order to maintain and improve innovative work behavior of employees. In addition, aspects of self-efficacy and psychological empowerment also need to be considered to encourage optimal innovative work behavior. Thus, this study contributes to the understanding of the factors that influence the innovative work behavior of employees in state banks, as well as providing direction for company management in improving performance and innovation in the work environment.